Risk factors for hypoxic–ischemic encephalopathy in cases of severe acidosis: A case–control study. (26th March 2022) - Lorain, Perrine; Bower, Alexandra; Gottardi, Elsa; Dommergues, Marc; Foix L'Helias, Laurence; Guellec, Isabelle; Kayem, Gilles
Abstract: Introduction: The aim of the study was to identify the obstetric risk factors for hypoxic–ischemic encephalopathy (HIE) in infants with asphyxia at birth. Material and methods: This multicenter case–control study covered the 5‐year period from 2014 through 2018 and included newborns ≥36 weeks of gestation with an umbilical pH at birth ≤7.0. Cases were newborns who developed moderate or severe HIE; they were matched with controls with pH ≤7.0 at birth over the same period without moderate or severe HIE. The factors studied were maternal, gestational, intrapartum, delivery‐related, and neonatal characteristics. A multivariable analysis was performed to study the maternal, obstetric, and neonatal factors independently associated with moderate or severe HIE. Results: Our review of the records identified 41 cases and 98 controls. Compared with controls, children with moderate or severe HIE had a lower 5‐min Apgar score, lower umbilical artery pH, and higher cord lactate levels at birth and at 1 h of life. Obstetric factors associated with moderate or severe HIE were the occurrence of an acute event (adjusted odds ratio [aOR] 6.4; 95% confidence interval [CI] 1.8–22.5), maternal fever (aOR 3.5; 95% CI 1.0–11.9), and thick meconium during labor (aOR 2.9; 95% CI 1.0–8.6). Conclusions: HIE is associated with a lower 5‐min Apgar score and with the severity of acidosis at birth and at 1 h of life. In newborns with a pH <7.0 at birth, the occurrence of an acute obstetric event, maternal fever, and thick meconium are independent factors associated with moderate or severe HIE.